ETIKA DALAM TEKS LONTAR KUMARA TATTWA - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
TRACT Ethics is knowledge of decency. Decency is in the form of rules that contain prohibitions or orders to do something. Thus in ethics we will find teachings about good deeds and bad deeds. Good deeds are to be carried out and bad deeds are avoided, of course ethics in Hinduism is a religious norm used as a starting point for thinking. such patterns of belief, philosophies of Hindu religion have a very important position in Hindu ethics. In Tutur Kumaratatwa, it is also mentioned, if we can control our appetite, we will get a state of silence, not moving, all lust will die, such as: adi astiti, pasingidan, henang-hening, tutur amunah carma, and lina. Besides that, to be able to become a wise man and have noble character, it is necessary to apply the teachings that exist in Hinduism, such as the Trikaya Parisudha, Panca Yama and Nyama Brata, and Dasa Yama and Niyama Brata. Keywords: Ethical Values, Lontar Kumara Tattwa, Controlling lust